Deny and Attack or Concede and Correct? Image Repair and the Politically Scandalized. Issue 3 (3rd July 2018) - Johnson, Tyler
Abstract : In the wake of recent political scandals, pundits have argued that the way a politician reacts to a scandal can make or break said politician's relationship with constituents and future in elected office. Some politicians concede guilt immediately, apologize, promise to take corrective action, and possibly open the door to moving on with their careers. Others deny culpability and attack their accusers, hoping to quickly put accusations behind them, change the subject, and channel public attention in a different direction. Does conceding guilt after a scandal breaks and offering to take corrective action to solve the problem help ameliorate the issue, or does it push the public away even further? Does denying involvement in a scandal and attacking the accuser compound the problem, or can it evoke positive feelings? This research uses an experimental design to test individuals' reactions to how politicians act after being accused of a personal scandal (in this case, an inappropriate relationship with a staffer). Results illustrate that a strategy involving denial and attacking accusers can spur positive evaluations of who a politician is and what that politician will do in the future, while the performance of conceding and taking corrective action is mixed at best.